Do the Throat Auroras Create Polar Cap Patches?. Issue 7 (7th April 2023) - Zhang, Duan; Zhang, Qing‐He; Oksavik, Kjellmar; Xu, Tong; Xing, Zan‐Yang; Lyons, L. R.; Han, De‐Sheng; Zhang, Hong‐Bo; Ma, Yu‐Zhang; Hu, Ze‐Jun; Liu, Jian‐Jun; Wang, Yong; et al.
Abstract: Throat auroras and polar cap patches are common phenomena in the polar ionosphere resulting from magnetosphere‐ionosphere coupling. A campaign was organized, with all‐sky imagers at Yellow River Station, the European Incoherent Scatter Svalbard Radar, and coordinated low‐altitude spacecraft observations. During periods of radial interplanetary magnetic field (IMF), observations showed that, as poleward moving throat auroras faded around the polar cap boundary, they linked to poleward moving ionization patches. The throat auroras were produced by soft‐electron precipitation associated with dayside magnetic reconnection. The red line emission intensity of throat auroras was correlated with dayside reconnection events. Dense plasma from lower latitudes was transported poleward via enhanced convection in the throat auroras to form patches. This is a potentially new formation mechanism for patches associated with throat auroras and magnetic reconnection for radial IMF. Moreover, the patches move anti‐sunward due to the E × B drift. Plain Language Summary: The polar ionosphere is a key region in the solar wind‐magnetosphere‐ionosphere coupling processes. The throat auroras and polar cap patches are important phenomenon in the polar ionosphere, and are associated with magnetopause dynamic processes. To clarify the relationship between throat auroras and patches, we organized a campaign of multiple instruments observations of Yellow River Station all‐sky imagers, European Incoherent Scatter Svalbard Radar, and low‐altitude spacecraft observations. We found that the throat auroras and patches were closely linked as they move poleward. The throat auroras were produced by soft‐electron precipitation associated with dayside magnetic reconnection for radial interplanetary magnetic field (IMF). We proposed a potentially new formation mechanism for patches from throat auroras under IMF Bx ‐dominant that high density plasma from lower latitudes was transported poleward via enhanced convection in the throat auroras to form patches. Moreover, the patches moved anti‐sunward due to the E × B plasma drift. Key Points: The formation of throat auroras and polar cap patches is studied with multiple instruments in space and on ground Both throat auroras and polar cap patches are closely linked as they move poleward The formation of throat auroras and patches is associated with magnetic reconnection for dominant radial interplanetary magnetic field